ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN ROA SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN MANUFAKTUR FOOD AND BEVERAGES YANG TERDAFTAR DI BEI TAHUN 2015-2017)”. - TRI MELDA MEI LIANA (JURNAL ILMIAH MAKSITEK, 2020)
This study aims to examine the direct and indirect effects of Total Asset Turnover (TATO) and Net Profit Margin (NPM) on Price to Book Value (PBV) as a proxy for the variable Firm Value with intervening Return on Assets (ROA). The samples of this study were 9 Food and Beverages manufacturing companies listed on the Indonesia Stock Exchange 2015-2017 using purposive sampling method. Data obtained from the official website of the Indonesia Stock Exchange in the form of annual reports and Company performance reports. The data analysis method used is panel data regression analysis and path analysis with the help of EViews 9 software. By using panel data regression analysis, it can be seen that Total Asset Turnover (TATO) and Net Profit Margin (NPM) have a positive and significant effect on Return on Assets (ROA). Total Asset Turnover (TATO) and Net Profit Margin (NPM) have a significant negative effect on Price to Book Value (PBV). Return on Asset (ROA) has a positive and significant effect on Price to Book Value (PBV). The results of the path analysis show that Total Asset Turnover (TATO) and Net Profit Margin (NPM) indirectly affect Firm Value (PBV) through Return on Assets (ROA).